Antimonene nanoribbon band-gap expansion : bond contraction and edge quantum entrapment - Wang, Sanmei (2020)
Combining the bond-order-length-strength corrected tight-binding (BOLS-TB) theory and the density functional theory (DFT) calculation, we clarified the energetic origin of the width-dependent band gap (Eg) expansion of the zigzag and armchair-edged antimonene nanoribbons (SbNRs) terminated by atomic hydrogen. Consistency between the density-function theory calculations and the BOLS-TB prediction affirmed that: (i) the Eg expansion originates from the Hamiltonian correction due to the size-dependent undercoordination effect; (ii) both the contraction of the ribbon up to 11% and the edge quantum trapping of charge of 0.05e determine the width dependent Eg change; and, (iii) Under-coordination induced quantum entrapment in the armchair SbNRs is stronger than that of zigzag SbNRs, resulting in larger Eg (∼0.3–0.6eV higher). Hence, the physical origin for the modulation of Eg (1.2–3.1 eV) by edge quantum entrapment or by other under-coordinated sites will benefit the Eg engineering of antimonene for wide electro-optical applications.